Eudaimonia Filsafat Dalam Kontemporer Dengan Memahami Kebahagiaan Menurut Aristoteles - Rasyidin, Nikita; Sitorus, Phil Fitzerald Kennedy (CV. ITTC INDONESIA, 2023)
Eudaimonia, derived from the Greek word, refers to the concept of happiness or success in life introduced by Aristotle. The term is traditionally translated as